Effect of seed priming with hydrogen peroxide on germination indices and seedling growth of wheat (Triticum aestivum L.) under salt stress condition - Seyed Keyvan Marashi; Zahra Albaji (علوم و فناوری بذر ایران)
This research was conducted as a factorial in a completely randomized design with four replications. The studied treatments include salinity stress in the form of irrigation with normal water (0.4) and with salinity of 4 and 8 dS/m of NaCl salt and seed priming with hydrogen peroxide, including no priming and seed priming in 25 and 50 mM solutions. In this experiment, the traits of germination percentage, germination rate, root length, stem length, root dry matter, stem dry matter and seed vigor index were investigated. In this research, the effect of salinity stress and hydrogen peroxide was significant on all investigated traits. The interaction effect of salinity stress and hydrogen peroxide on the studied traits was significant except germination rate. The maximum percentage of germination, length and dry matter of root and stem and seed vigor index was obtained under absence of stress (normal water) and application of 50 mM hydrogen peroxide and the minimum was under salinity of 8 dS/m and no application hydrogen peroxide. The maximum germination rate was obtained in the 50 mM hydrogen peroxide and no salt stress. In general, the results showed that the use of hydrogen peroxide in the presence of salinity stress was effective through the improvement of indices, and this can be considered as a strategy for better and proper seedling establishment.